Sulforaphane enhances the anticancer activity of taxanes against triple negative breast cancer by killing cancer stem cells - Burnett, Joseph P.; Lim, Gi; Li, Yanyan; Shah, Ronak B.; Lim, Rebekah; Paholak, Hayley J.; McDermott, Sean P.; Sun, Lichao; Tsume, Yasuhiro; Bai, Shuhua; Wicha, Max S.; Sun, Duxin; et al. (Cancer letters, 2017)
Triple negative breast cancer (TNBC) typically exhibits rapid progression, high mortality and faster relapse rates relative to other breast cancer subtypes. In this report we examine the combination of taxanes (paclitaxel or docetaxel) with a breast cancer stem cell (CSC)-targeting agent sulforaphane for use against TNBC. We demonstrate that paclitaxel or docetaxel treatment induces IL-6 secretion and results in expansion of CSCs in TNBC cell lines. Conversely, sulforaphane is capable of preferentially eliminating CSCs, by inhibiting NF-κB p65 subunit translocation, downregulating p52 and consequent downstream transcriptional activity. Sulforaphane also reverses taxane-induced aldehyde dehydrogenase-positive (ALDH+) cell enrichment, and dramatically reduces the size and number of primary and secondary mammospheres formed. In vivo in an advanced treatment orthotopic mouse xenograft model together with extreme limiting dilution analysis (ELDA), the combination of docetaxel and sulforaphane exhibits a greater reduction in primary tumor volume and significantly reduces secondary tumor formation relative to either treatment alone. These results suggest that treatment of TNBCs with cytotoxic chemotherapy would be greatly benefited by the addition of sulforaphane to prevent expansion of and eliminate breast CSCs. •Standard taxane-based treatment increases inflammatory cytokine secretion.•Paclitaxel and docetaxel enrich the CSC population.•Anti-CSC compound sulforaphane inhibits NF-κB transcriptional activity.•Sulforaphane reverses taxane-induced CSCs enrichment.•Combination greatly reduces primary tumor volume and secondary tumor formation.